Hypercoagulability following major partial liver resection ‐ detected by thrombomodulin‐modified thrombin generation testing - Potze, W.; Alkozai, E. M.; Adelmeijer, J.; Porte, R. J.; Lisman, T. (Alimentary pharmacology & therapeutics, 2015)
Summary Background Conventional coagulation tests are frequently prolonged after liver surgery, suggesting a post‐operative hypocoagulability. However, these tests are unreliable for assessment of the haemostatic status in these patients. In contrast, thrombin generation testing measures the true balance between pro‐ and anti‐coagulant factors. Aim To study the perioperative coagulation status in patients undergoing hemi‐hepatectomy using thrombin generation assays. Methods We examined thrombin generation profiles in serial plasma samples taken from seventeen patients undergoing right hemi‐hepatectomy. Results were compared to ten patients undergoing pancreatic resection and twenty‐four healthy volunteers. In addition, we measured conventional coagulation tests and plasma levels of several haemostatic proteins. Results Following liver resection, the endogenous thrombin potential (ETP) slightly decreased until post‐operative day 7. However, in the presence of thrombomodulin, the ETP increased [from 542 nM*min (417–694) at baseline to 845 nM*min (789–1050) on post‐operative day 3] to values higher than that in healthy subjects (558 nM*min (390–680); P < 0.001), which contrasts with substantially prolonged PT levels. Normal to decreased thrombin generation was observed following pancreatic resection. Thrombin generation was only slightly affected by thrombomodulin after hemi‐hepatectomy, while thrombin generation in healthy subjects decreased profoundly upon addition of thrombomodulin. This hypercoagulability following liver resection may be explained by decreased levels of protein C, S, and antithrombin and by elevated levels of factor VIII. Conclusions Thrombin generation in the presence of thrombomodulin revealed hypercoagulability in patients following liver resection. These results support the recently advocated restrictive use of plasma during liver resection and the exploration of more extensive use of post‐operative thrombosis prophylaxis.